Digital approach vs conventional approach in architectural design process for producing creative product - Isham Shah Hassan; Mohd Arif Ismail; Ramlee Mustapha (Proceedings of AICS - Social Sciences, 2013)
Design is a complex and open process. A designer starts the idea from an abstract form to a final idea in the form of a product to solve the design problem. At the early design stage discussion occurs regularly between students and lecturer to improve the design quality. The selection of a proper media for presentation is important in the design process to make sure the media selected has strong visual impact. CAD technology gives opportunity for students to use three dimensional digital models in the design process to develop good design concept. The digital model can decrease the aspect of abstraction on a design idea. The main objective of this study is to compare the development in the design activities between students that use digital studio and students that use conventional studio. The study had been done for four years on diploma architectural students at Port Dickson Polytechnic. All the semester six students had been selected as the sample for this study. The quasi experimental method was used to study the effect of integrating digital studio in the design process. The research outcome showed that significant difference between digital model product (M=80.2) compared to conventional product from the aspect of creativity, t(238) = 9.198 significant. This study shows that integration of digital studio in the learning process of design modules in polytechnic provides learning environment that ignites students to produce creative architectural design product.Keywords: CPAM, CAD Technology, Design Process, Creative Product